Allogenic and autogenic controls on facies and stratigraphic architecture of the Lower Jurassic Mashabba Formation, Gebel Al-Maghara, North Sinai, Egypt - Ghandour, Ibrahim M.; Fürsich, Franz (Proceedings of the Geologists Association, 2022)
The Lower Jurassic Mashabba Formation crops out in the core of the doubly plunging Al-Maghara anticline, North Sinai, Egypt. It represents a marine to terrestrial succession deposited within a rift basin associated with the opening of the Neotethys. Despite being one of the best and the only exposed Lower Jurassic strata in Egypt, its sedimentological and sequence stratigraphic framework has not been addressed yet. The formation is subdivided informally into a lower and upper member with different depositional settings and sequence stratigraphic framework. The sedimentary facies of the lowermember include shallow-marine, fluvial, tidal flat and incised valley fill deposits. In contrast, the upper member consists of strata with limited lateral extension including fossiliferous lagoonal limestones alternating with burrowed deltaic sandstones. The lowermember contains three incomplete sequences (SQ1-SQ3). The depositional framework shows transgressive middle shoreface to offshore transition deposits sharply overlain by forced regressive upper shoreface sandstones (SQ1), lowstand fluvial to transgressive tidal flat and shallow subtidal sandy limestones (SQ2), and lowstand to transgressive incised valley fills and shallow subtidal sandy limestones (SQ3). In contrast, the upper member consists of eight coarsening-up depositional cycles bounded by marine flooding surfaces. The cycles are classified as carbonate-dominated, siliciclastic-dominated, and mixed siliciclastic-carbonate. The strata record rapid changes in accommodation space. The unpredictable facies stacking pattern, the remarkable rapid facies changes, and chaotic stratigraphic architecture suggest an interplay between allogenic and autogenic processes. Particularly syndepositional tectonic pulses and occasional eustatic sea-level changes controlled the rate and trends of accommodation space, the shoreline morphology, the amount and direction of siliciclastic sediment input and rapid switching and abandonment of delta systems. (c) 2021 The Geologists' Association. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2022-03-11